2017
DOI: 10.1080/0284186x.2017.1346384
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CT-verified loco-regional recurrences after definitive IMRT for HNSCC using site of origin estimation methods

Abstract: For recurrences identified by possible points of recurrence origin, no significant difference between observer-based or mathematically estimated methods was found. More than half of T-site recurrences were inside high-dose treatment volume, whereas N-site recurrences were mainly outside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…In Denmark, a national storage facility of DICOM data has been established [8]. It is currently used by a number of clinical trials [9][10][11][12][13] and contains radiotherapy information from more than 5000 patients. This study focuses on the largest clinical trial in the data bank; a clinical randomized trial on hypo-fractionation from the Danish Breast Cancer Group (DBCG) with 1883 patients, of which 1550 patients were Danish.…”
Section: Introductionmentioning
confidence: 99%
“…In Denmark, a national storage facility of DICOM data has been established [8]. It is currently used by a number of clinical trials [9][10][11][12][13] and contains radiotherapy information from more than 5000 patients. This study focuses on the largest clinical trial in the data bank; a clinical randomized trial on hypo-fractionation from the Danish Breast Cancer Group (DBCG) with 1883 patients, of which 1550 patients were Danish.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with existing literature, reporting locoregional failures to predominantly occur in high-dose volumes for both the older 3D ( 27 ) and more conformal RT techniques ( 28 43 ). Compared with previous studies, our analysis provides a larger patient cohort ( 22 , 23 , 27 , 31 , 32 , 39 , 43 ) and longer median follow-up time ( 22 24 , 30 32 , 35 , 39 ). Leeman et al.…”
Section: Discussionmentioning
confidence: 97%
“…The determination of out-of-field failures, defined as failure that occurred outside the treatment field, is fairly straightforward in published reports. The definition of a marginal failure is, however, not as clear-cut ( 22 , 30 , 31 , 39 ). In the current study, we defined marginal failure as a situation in which at least one-half of the volume of the recurrence appeared to be outside the original tumor site (CTVp or CTVn) ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prospective randomized DAHANCA 19 trial investigated the benefit of adding the EGFR-inhibitor zalutumumab to radiotherapy for squamous cell carcinoma of the head and neck (H&N) and enrolled patients from 2007 to 2012 [7] from six radiotherapy treatment centers. The results presented at ESTRO37 showed that zalutumumab did not improve loco-regional tumor control or survival, but resulted in more treatment related toxicity [8][9][10].…”
Section: Patients and Contoursmentioning
confidence: 99%